Cultivating the wild: strategies for entrepreneurs navigating niche and specialty food markets - Malone, Trey; Cooper, Courtney F. (Frontiers in Sustainable Food Systems, 2025)
IntroductionConsumer demand for authenticity and sustainability in food systems is growing, creating both opportunities and challenges for entrepreneurs in niche and specialty markets. While wild-foraged and hunted foods are often perceived as more “natural” and sustainable, attempts to scale these products through farming may compromise their perceived authenticity.MethodsTo explore these dynamics, we conducted discrete choice experiments with a nationally representative sample of 1,039 U.S. consumers. Participants evaluated their willingness to pay (WTP) for salmon, venison, and morel mushrooms, presented in both wild-foraged/hunted and farm-raised forms.ResultsConsumers exhibited strong preferences for wild versions of all three products, with average premiums of 5.09 for salmon, 7.47 for venison, and 4.73 for morels. Perceptions of naturalness and minimal human intervention largely drove these premiums. Additional attitudinal predictors of WTP included concern for animal welfare, distrust in government regulation, and identification with foodie culture. However, these preferences reflected characteristics that consumers cannot verify, suggesting that scaling via farming may reduce market value by undermining product authenticity.DiscussionOur findings highlight an “authenticity paradox”: while wildness drives consumer demand, efforts to commercialize and expand production may erode the very attributes that generate value. Entrepreneurs in niche food markets must carefully balance ecological sustainability, product scaling, and consumer trust. Strategic messaging and transparent sourcing practices may help preserve perceived authenticity while enabling market growth.